PIECES Framework dalam Analisis Penerapan Sistem Informasi - Mutiana Pratiwi; Ulya Ilhami Arsyah; Devia Kartika; Rahmatul Husna Arsyah (Universitas Putra Indonesia YPTK Padang, 2021)
The application of information technology is currently widely used by agencies in carrying out various operational activities. This study tries to apply the PIECES Framework to the analysis of information systems. To implement it, it is necessary to test responses from users on an information system. The system to be tested is the information system of Mako Battalion 131 Braja Sakti. The information system used to support the performance of soldiers where the responsible in this case is part of the operations staff. In their service, the operations staff collect data from each company. The data is inputted into the online-based ANEV DATA system. The system will later be used in processing soldier certification data. PIECES focuses on 6 focus areas of analysis, namely performance, information and data, economy, control and security, efficiency, and service. The purpose of this study is the application of the PIECES Framework in analyzing the quality of the implementation of information systems to ensure the success targeted by the operations staff. This study uses interviews and observations as well as the distribution of questionnaires as a method of data collection. The results of this study indicate that the use of ANEV Data as an information system to improve performance gets an average result at the Performance level of 5.20, information and data level of 4.76, economic indicator level of 5.20, Control indicator level of 4.85, and efficiency level of 4.16. and service satisfaction of 7.16. The value of the operation staff is very satisfied using the ANEV Data information system.